Differential value of external anal- and urethral-sphincter electromyography in multiple system atrophy cerebellar type and spinocerebellar ataxias. (October 2020) - Miao, Yan; Wang, Kunyu; Han, Jinming; Wang, Zhiwei; Bian, Yang; Guo, Qifeng; Sun, Chenjing; Wang, Qingqing; Song, Dandan; Qi, Xiaokun; Qiu, Feng
Highlights: Differentiating MSA-C and SCAs is challenging. EAS-EMG may be helpful for early differential diagnosis of MSA-C and SCAs. US-EMG could be a complementary method for males when EAS-EMG is not available. Abstract: Objective: Clinically differentiating multiple system atrophy cerebellar type (MSA-C) and spinocerebellar ataxias (SCAs) is challenging, especially at early disease stages, because of their similarities in clinical manifestation and imaging results. The purpose of this study was to explore the value of external anal-sphincter electromyography (EAS-EMG) and urethral-sphincter electromyography (US-EMG) for distinguishing between MSA-C and SCAs. Methods: A total of 51 subjects, including 33 MSA-C and 18 SCAs, were recruited. Average duration and amplitude of motor unit potentials (MUPs), percentage of polyphasic MUPs, amplitude during strong contraction and recruitment pattern during maximal voluntary contraction were recorded and analyzed to identify differential diagnostic results of EAS-EMG and US-EMG for MSA-C and SCAs. Results: Significant differences in average MUP duration, percentage of polyphasic MUPs, and ratio of simple phase and simple-mix phase using EAS-EMG were noted between patients with MSA-C and SCAs. These same parameters also differed significantly between MSA-C and SCAs male patients using US-EMG. Conclusions: EAS-EMG may serve as a potential method for early differential diagnosis between patients with MSA-C and SCAs. Furthermore, US-EMG could be a supplementary method for males when EAS-EMG is not available.